2016
DOI: 10.3109/10641955.2015.1100308
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and antenatal risk factors for postpartum-onset hypertensive disorders

Abstract: Careful monitoring of blood pressure should be considered for women with the identified risk factors even after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Our results are broadly consistent with those of prior investigations [11, 13]. Using a retrospective case-control study with 34 cases and 68 controls and the same definition of PPPE as our study, Bigelow et al identified BMI at delivery, age >40 years, a diagnosis of gestational diabetes in the index pregnancy, Black race and Latino ethnicity as risk factors [11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are broadly consistent with those of prior investigations [11, 13]. Using a retrospective case-control study with 34 cases and 68 controls and the same definition of PPPE as our study, Bigelow et al identified BMI at delivery, age >40 years, a diagnosis of gestational diabetes in the index pregnancy, Black race and Latino ethnicity as risk factors [11].…”
Section: Discussionsupporting
confidence: 91%
“…In a recent retrospective study performed in Japan [13], Takaoka et al also examined demographic risk factors for PPPE, defined as the onset of hypertension after a normotensive pregnancy, after delivery, including cases occurring within the first 48h postpartum. In this study, pre-pregnancy BMI above 25kg/m 2 , c-section and use of assisted reproductive technologies, presence of chronic nephritis, hypothyroidism and blood pressures (BP) in the high normal range (SBP≥130 mm Hg or DBP≥ 85 mm Hg) at the first prenatal visit (before 14 weeks gestation) or before delivery were found to be independent risk factors for PPPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some women with pregnancies complicated by GH-PE will have persistent postpartum chronic hypertension (CHTN) [8,21]. Previous studies have revealed that older age, pre-existing chronic hypertension, smoking, pre-pregnancy obesity (elevated body mass index [BMI]), and co-morbidities such as thyroid disorders are common risk factors for postpartum CHTN [22,23]. Obesity [10,12,16] and excessive weight gain [17] are risk factors for elevated BP, resulting from chronic inflammation, oxidative stress, and placental endothelial cell activation [10,12,16].…”
Section: Ivyspringmentioning
confidence: 99%
“…Obesity [10,12,16] and excessive weight gain [17] are risk factors for elevated BP, resulting from chronic inflammation, oxidative stress, and placental endothelial cell activation [10,12,16]. However, most of explored risk factors for CHTN are pre-pregnancy factors, based on studies with small sample sizes (< 2,000 GH-PE women) [22,23].…”
Section: Ivyspringmentioning
confidence: 99%